A game-theoretic strategic mechanism to control brand counterfeiting. Issue 5 (3rd May 2018) - Zameer, Hashim; Wang, Ying; Yasmeen, Humaira; Mofrad, Amirhossein Akhavan; Saeed, Rashid
Abstract : Purpose: The purpose of this paper is to design a game theory based model that not only provide theoretical basis to control brand counterfeiting, but it also provide a mechanism to enhance brand revenue. Design/methodology/approach: This study used the dynamic game theory of incomplete information to understand and encounter the brand counterfeiting issues. The study analyzed the economic relationship of legitimate brand, counterfeiter and consumers using mixed strategy of the dynamic game theory of incomplete information. Findings: The results have indicated that brands those take countermeasures to reduce counterfeiting earn maximum revenue, even when the legitimate brands and consumers are unaware from the actions of counterfeiting firms, the legitimate brands should take countermeasures to reduce counterfeiting to earn maximum revenue, and there exists optimal anti-counterfeiting cost for the legitimate brand. Further, this study provides theoretical basis where brand managers can decide to adopt or not to adopt anti-counterfeiting strategy, and also indicate the consequences of each decision. Practical implications: Based upon the findings, the study put forward valuable managerial implications. The study revealed that the legitimate brand must emphasize on the significance of taking countermeasures against counterfeiter and also, brand managers should focus on making product traceable, empowering the consumer and ensuring coordination with government officials to control the counterfeiting issues. Originality/value: This paper incorporates the role of legitimate brand, counterfeiter and a consumer to establish the dynamic game theory model using mixed strategy to understand and address the counterfeiting issues in the global market.